THE INFLUENCE OF IMPELEMENTING THE ACCOUNTANT'S CODE OF ETHICS AND EMOTIONAL INTELLIGENCE FOR THE ACCOUNTANT PROFESSION IN DECISION MAKING - Angelia, Shella; Salim, Susanto (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this paper is to determine the influence of accountant code of ethics and emotional intelligence on decision making in the accounting profession at Bank Central Asia. This study uses an associative approach that aims to determine the relationship of a variable with other variables so that it can control or anticipate a problem that may occur. The population selected in this study is the accountant profession at Bank Cenntral Asia in Jakarta City. The collection technique applied is by distributing questionnaires to research respondents. This study applied multiple linear regression research method. The results of this study partially state that the accountant's code of ethics has an influence on decision making. On the other hand, emotional intelligence has no influence on decision making. Simultaneously, professional ethics and emotional intelligence have an influence on decision making.